2011
DOI: 10.1002/jbm.b.31936
|View full text |Cite
|
Sign up to set email alerts
|

Influence of femtosecond laser treatment on shear bond strength of composite resin bonding to human dentin under simulated pulpal pressure

Abstract: This in vitro study evaluated the influence of femtosecond laser (fs-laser)-generated patterns on shear bond strength (SBS) of composite resin bonded to human dentin under simulated pulpal pressure. Laser treatment was used to produce two different patterns on dentin surfaces. Three test groups and a control group without laser treatment under pulpal pressure were investigated. Dentin discs of 800 nm thickness were cut from 60 extracted caries-free human molars. Using a perfusion machine, the discs were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…As regards to the storage medium to preserve teeth after extraction until its use in the experimental procedures, most of the authors reported the use of thymol [ 15 , 17 , 18 , 25 , 28 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], chloramine [ 13 , 14 , 23 , 26 , 27 , 29 , 30 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards to the storage medium to preserve teeth after extraction until its use in the experimental procedures, most of the authors reported the use of thymol [ 15 , 17 , 18 , 25 , 28 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], chloramine [ 13 , 14 , 23 , 26 , 27 , 29 , 30 , …”
Section: Resultsmentioning
confidence: 99%
“…The majority of the authors [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 58 , 59 , 60 , 61 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 ,…”
Section: Resultsunclassified
“…To detect a difference between the groups, a sample of 15 dentine discs per test and control group was necessary to have an 80% power at alpha = 0.05 [19]…”
Section: Treatment Of Results and Statistical Analysismentioning
confidence: 99%
“…From a clinical point of view, mean SBS values are less relevant than the likelihood that strong adhesion will be achieved with a given system or that its bond strength will be low and the risk of adhesive failure high [19]. The Weibull distribution takes this probabilistic approach of adhesive evaluation into account.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation